PENYULUHAN BANGUNAN RUMAH TAHAN GEMPA SEBAGAIOPTIMALISASI MITIGASI GEMPA BUMI - Yulianto Purwono Prihatmaji (Asian Journal of Innovation and Entrepreneurship, 2013)
Indonesian territory includes areas that have a high level of seismic risk amongseveral world diseIuruh earthquake area. Recentdata were successfully recorded showsthat on average every ten tehun happened earthquake activity that resulted inconsiderable damage in Indonesia. Most occur in offshore areas, and partly to the areapemukiman.Pada fairly dense residential areas, needs to be a protection to reduce themortality rate of the population and severe damage due to shock gempa.Tedunan apermanent occupancy programmed together government private parties, which aims toprovide decent houses and in accordance with the conditions in the area tedunan itself.Tedunan hamlet located in Central Java region potentially earthquake originating fromthe Mount Merapi. This causes Tedunan areas into areas that are prone to volcanic andtectonic tremor, associated with the status of Mount Merapi, which became one of themost active volcanoes in the world and the island of Java is an area of active tectonicplates. Thus, dicanangkanlah program Counseling Barataga (House Seismic) to shareknowledge, and to increase the vocabulary knowledge of citizens Tedunan about buildingearthquake resistant houses as well as shape optimization of mitigating earthquake witha stage extension development techniques earthquake-resistant housing, training, anddiscussion forums ,